2010
DOI: 10.1016/j.bcp.2009.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Mevalonate pathway intermediates downregulate zoledronic acid-induced isopentenyl pyrophosphate and ATP analog formation in human breast cancer cells

Abstract: To cite this version:Johanna Räikkönen, Hannu Mönkkönen, Seppo Auriola, Jukka Mönkkönen. Mevalonate pathway intermediates downregulate zoledronic acid-induced isopentenyl pyrophosphate and ATP analog formation in human breast cancer cells. Biochemical Pharmacology, Elsevier, 2009, 79 (5) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 45 publications
2
41
0
Order By: Relevance
“…The addition of GGPP but not FPP into ZOL-treated cells resulted in an almost complete inhibition of IPP accumulation through the down regulation of HMGCoA reductase in addition to rescuing small GTPases prenylation. 44) Similar results were also obtained with FLU-treated cells (Figs. 3A, B), where the addition of GGPP completely reversed FLU-induced antiproliferative effect.…”
Section: )supporting
confidence: 79%
See 1 more Smart Citation
“…The addition of GGPP but not FPP into ZOL-treated cells resulted in an almost complete inhibition of IPP accumulation through the down regulation of HMGCoA reductase in addition to rescuing small GTPases prenylation. 44) Similar results were also obtained with FLU-treated cells (Figs. 3A, B), where the addition of GGPP completely reversed FLU-induced antiproliferative effect.…”
Section: )supporting
confidence: 79%
“…The molecular mechanism of NBPs is usually due to the inhibition of FPP synthase and loss of signaling in the downstream pathway of small GTPases, such as Ras proteins. 16,43) Previous studies showed that a consequence of FPP synthase inhibition by ZOL is the accumulation of intracellular isopentenyl pyrophosphate (IPP), which leads to the formation of pro-apoptotic ATP analogue APPPI (triphosphoric acid 1-adenosin-5′-yl ester 3-(3-methylbut-3-enyl)ester) inducing apoptosis 44,45) (Fig. 5).…”
Section: )mentioning
confidence: 99%
“…The mevalonate pathway is a biosynthetic pathway responsible for the production of cholesterol and isoprenoid lipids, particularly the farnesyl-and geranylpyrophosphates which are required for the prenylation of small GTP proteins that play crucial roles in signalling pathways controlling cell growth. Inhibition of the mevalonate pathway has been proposed as being the fundamental molecular mechanism of many of the observed anti-cancer effects of N-BPs, such as ZA, both in vitro and in vivo [ 12 ] . After FPPS inhibition by N-BPs, the pathway is blocked and inhibition of protein prenylation occurs as a result of the lack of FPP and GGPP enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…2), suggesting that ZOL induced apoptosis at least in part. Pandha et al and Ullén et al reported that ZOL induced apoptotic cell death in a caspase-dependent manner; however, they did not examine the involvement of the mevalonate pathway (20,21), although there have been reports suggesting that the mevalonate pathway is important for the mechanisms of cell death induced by bisphosphonates in multiple myeloma, prostate cancer and breast cancer (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%